Real Time Econometrics - M. Hashem Pesaran; Allan Timmermann (Center for Economic Studies and ifo Institute (CESifo), 2004)
This paper considers the problems facing decision-makers using econometric models in real time. It identifies the key stages involved and highlights the role of automated systems in reducing the effect of data snooping. It sets out many choices that researchers face in construction of automated systems and discusses some of the possible ways advanced in the literature for dealing with them. The role of feedbacks from the decision-maker's actions to the data generating process is also discussed and highlighted through an example.
Keywords: 330; specification search; data snooping; recursive/sequential modelling; automated model selection